IMPACT OF GLOBALIZATION ON PAINTING: वैष्वीकरण का चित्रकला पर प्रभाव - Sharma, Archana (International Journal of Research -GRANTHAALAYAH, 2014)
Art plays an important role in the development of any country. Art is considered a medium for realizing beauty or prosperity. Architecture, sculpture, painting and music have been considered under fine arts. Both painting or poetry is a means of expressing the inner feelings of man. Today in painting, it is possible that even if color does not make sense, it can reach the mind directly and make you feel happy. Art is said to be a response to the realization of truth. By combining Rupo in pictures, the eyes get satiety. Through the eyes, there is a cook in different minds in the mind of the audience. किसी भी देष के विकास में कला का महत्वपुर्ण योगदान होता है। कला को सोन्दर्य अथवा समृद्वि को साकार करने का माध्यम माना गया है। वास्तुकला, मूर्ति कला, चित्रकला तथा संगीत को ललित कला के अन्तर्गत माना गया है। चित्रकला हो या कविता दोनो ही मनुष्य की आंतरिक भावनाओं को व्यक्त करने का एक माध्यम है। चित्रकला में आज ऐसा संभव है कि रंग का अर्थ न निकले फिर भी वह सीधे मन तक पहुॅच कर रसानुभूति करा सकता है। कला को सत्य की अनुभूति की अनुक्रति कहा गया है। चित्रो में रूपो के संयोजन से नेत्रो को तृप्ति मिलती है। आंखो के माध्यम से दर्षक के मन में विभिन्न भावो से रसोदे्रक होता है।